Exploring the Value of Mutual Cooperation in Religious Celebrations: A Case Study of the Celebration Maulid Nabi Muhammad SAW - Heridianto, Heridianto (IJoIS: Indonesian Journal of Islamic Studies, 2025)
This study examines the role of religious celebrations and local wisdom in fostering community solidarity and cultural preservation in Indonesia. The background of this research is rooted in the importance of religious traditions and rituals, which not only serve as a means of spiritual reflection but also as an important component in strengthening social bonds in society. The purpose of this study is to analyze how religious practices, such as Eid al-Fitr and the Prophet's Birthday, contribute to strengthening local wisdom values, including mutual cooperation, social concern, and respect for the environment. This research uses a qualitative approach, focusing on community-based traditions, interviews, and participant observations to capture the cultural dynamics surrounding these celebrations. The results revealed that these religious events are not only an expression of faith but also play a key role in promoting social cohesion through collective activities such as sharing food, praying together, and exchanging support. These practices encourage the transmission of intergenerational values such as humility, cooperation, and empathy. In conclusion, this study highlights the deep relationship between religious celebrations and local wisdom, which suggests that these traditions are important for maintaining social harmony and cultural identity in contemporary Indonesian society. These findings also emphasize the importance of preserving these traditions as a way to strengthen spiritual and societal ties in the midst of globalization and modernization.